Low-input cultivation of camelina (Camelina sativa (L.) Crantz) in a Mediterranean semi-arid environment - Giovanni Avola; Orazio Sortino; Fabio Gresta (Italian Journal of Agronomy, 2021)
The cultivation of oil crops for biofuel production has often been accused of not being